Poly(ADP-Ribose)Polymerase-1 in Lung Inflammatory Disorders: A Review - Sethi, Gurupreet S.; Dharwal, Vivek; Naura, Amarjit S. (Frontiers in Immunology, 2017)
Asthma, acute lung injury (ALI) and chronic obstructive pulmonary disease (COPD) are lung inflammatory disorders with a common outcome, that is, difficulty in breathing. Corticosteroids, a class of potent anti-inflammatory drugs, have shown less success in treatment/management of these disorders, particularly ALI and COPD; thus, alternative therapies are needed. Poly (ADP-ribose) polymerases (PARPs) are the post-translational modifying enzymes with a primary role in DNA repair. During last two decades, several studies have reported critical role of PARPs in number of inflammatory disorders. In current review, we have discussed studies which address the role of PARPs in asthma, ALI and COPD. Among the different members of the family, PARP-1 emerges as a key player in orchestration of lung inflammation in asthma and ALI. In addition, PARP activation seems to be associated with the progression of COPD. Furthermore, PARP-14 seems to plays a crucial role in asthma. STAT-6 and GATA-3 are reported to be central players in PARP-1 mediated eosinophilic inflammation in asthma. Interestingly, oxidative stress-PARP-1-NF-κB axis appears to be tightly linked with inflammatory response in all three-lung diseases despite their distinct pathos-physiologies. The review shed light on PARP-1 regulated factors, which may be common or differential players in asthma/ALI/COPD and put forward our prospective for future studies.